1991
DOI: 10.1017/s0954579400005290
|View full text |Cite
|
Sign up to set email alerts
|

Mothers with zero Beck depression scores act more “depressed” with their infants

Abstract: Mothers who scored zero on the Beck Depression Inventory (N = 25) were compared to “depressed” mothers (high scores on the Beck) (N = 39) and nondepressed mothers (N = 98) during face-to-face interactions with their 5-month-old infants. The interaction videotapes were rated on the Interaction Rating Scales and were coded second-by-second for attentive/affective behavior states. The zero Beck mothers and their infants received lower ratings and were in less positive behavior states (alone or together) than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
6

Year Published

1993
1993
1999
1999

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 17 publications
3
36
0
6
Order By: Relevance
“…Based on the BDI scores, families were screened (N ϭ 284) until 20 families of each type were enrolled in the study. Parents with scores 0 -2 were excluded in this study (9% of sample screened) because these types of parents were found to behave in a more "depressed" fashion than high BDI scoring parents in a previous study (Field, Morrow, Healy, Foster, Adlestein, & Goldstein, 1992)and parents with scores of 10 -16 (4% of sample screened) were excluded to more clearly demarcate the nondepressed and depressed groups. Families were screened until 20 families of each type were enrolled in the study.…”
Section: Subjectsmentioning
confidence: 99%
“…Based on the BDI scores, families were screened (N ϭ 284) until 20 families of each type were enrolled in the study. Parents with scores 0 -2 were excluded in this study (9% of sample screened) because these types of parents were found to behave in a more "depressed" fashion than high BDI scoring parents in a previous study (Field, Morrow, Healy, Foster, Adlestein, & Goldstein, 1992)and parents with scores of 10 -16 (4% of sample screened) were excluded to more clearly demarcate the nondepressed and depressed groups. Families were screened until 20 families of each type were enrolled in the study.…”
Section: Subjectsmentioning
confidence: 99%
“…Infants of mothers who scored zero to two on the CES-D were not included in the study (N ϭ 2) because lowscoring mothers have been noted to exhibit more depressive symptoms such as lower activity levels, lesser expressivity, and less frequent vocalizing than high scoring mothers, and thus are thought to be denying their symptoms or showing a "faking good" syndrome (Field et al, 1992;Lyons-Ruth, Zoll, Connell, & Grunebaum, 1986;Scafidi, Field, Prodromidis, Abrams, 1995).…”
Section: The Center For Epidemiological Studies-depression Index (Ces-d)mentioning
confidence: 99%
“…These classification criteria are commonly used in research studies on depressed adults (Coyne and Gotlib, 1983). Mothers with 0-2 scores (N=9) were omitted because they have been noted to look depressed more than highxoring mothers (despite their low scores) and because they may be different from both the depressed and nondepressed mother groups (Field et al, 1992). Because we were interested in the effects of current depressive symptoms, we classified the mothers according to their scores when their infants were 3 months old.…”
Section: Subjectsmentioning
confidence: 99%